Cognitive impairment in Sjogren’s syndrome: Interplay between BACE1 activity, inflammatory blood biomarkers and neurocognitive testing - Alireza Kooshki; Mohammad Yousefi; Reyhane Farmani; Hamid Kabiri-Rad; Hossien Nezami; Amirhosein Zardast; Zeinab Saremi (PLoS ONE, 2025)
Background Sjogren’s syndrome (SS) is considered as a chronic, autoimmune disorder, that can present with various manifestations both intra and extra-glandular. Cognitive dysfunction is pivotal in recognizing neurological complications in SS. Methods A study involving 44 SS cases and 37 controls was conducted to evaluate cognitive dysfunction further. Participants underwent multiple cognitive tests and blood tests for evaluation. Also, the β-site amyloid precursor protein cleaving enzyme 1 (BACE1), Interleukin 6 (IL-6), total antioxidant capacity (TAC), nitric oxide (NO), and malondialdehyde (MDA) serum levels were measured. Multiple analyses were done by PRISM 10 and SPSS 22. Results The MoCA and SDLT scores were lower in Sjogren patients (P < 0.001). Serum BACE1, IL-6, NO, TAC, and MDA did not statistically vary in the SS patients. The only variables varied by medication therapy with methotrexate (MTX), hydroxychloroquine (HCQ), and prednisone were WBC count (P = 0.03) and triglyceride levels (in MTX and HCQ, P = 0.04), with no effect on neurocognitive factors. IL-6 was strongly correlated with the duration of symptoms (r = 0.99, P-value < 0.001). BACE1 had a positive correlation with IL-6 level (r = 0.4, P-value = 0.027). Conclusion SS patients demonstrated significantly lower performance in neurocognitive tests, while BACE1 and inflammatory markers were not altered. This indicates that cognitive decline in SS is present but the mechanism still requires further evaluation. MTX, HCQ, and Prednisone use did not alter neurocognitive factors. Important correlations were found between hematological and cognitive tests in this study which provides new insights in the field of SS.